Kajian Ayat Makkiyah dan Madaniyah Menurut Pemikiran Orientalis dan Oksidentalis - Sarnoto, Ahmad Zain; Hariyadi, Muhammad; Adhariani, Dwi Eka (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article discusses the study of makkiyah and madaniyah verses in the Qur'an through the perspective of orientalist and occidentalist thought. The makqiyah verse, which was revealed in Mecca before the hijrah, emphasizes more on the theme of faith and morality, while the madaniyah verse, which was revealed after the hijrah in Medina, focuses more on social and legal aspects. Using a descriptive qualitative approach, this study collected data from a variety of literature, including books, journal articles, and research reports. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the difference between the two lies not only in the themes raised, but also in the much more complex way of understanding the text, reflecting the social and political context in which the verses are revealed. This article concludes that a deeper understanding of the Qur'an needs to be established through dialogue between these two perspectives in order to achieve a more comprehensive and relevant understanding in the present day.